Bifunctional superparamagnetic–luminescent core–shell–satellite structured microspheres: preparation, characterization, and magnetodisplay application. Issue 18 (14th May 2015) - Li, Chung-Lin; Huang, Bohr-Ran; Chang, Jia-Yaw; Chen, Jem-Kun
<x xml:space="preserve">Abstract</x> Bifunctional superparamagnetic–luminescent core–shell–satellite structured microspheres are prepared by a layer-by-layer assembly between metal cations and thiol groups for magnetodisplay applications.